Eve in front of the mirrow. Educating in the recognition and vindication of Muslim women through the cinema - Barrenetxea Marañón, Igor (Clio. History and History Teaching, 2020)
Though the Muslim woman is still strongly discriminated, there are some very interesting and intriguing areas for vindication and visibility, one such is cinema.This article, hence, shows how the issues, conditions and realities of women in the Islamic world can be shown and worked in the classroom. And, at the same time, it is not only an incitement to the recognition of this figure, but also a very correct way to encourage a mentality change which will help to understand their rough and bitter reality, while raising in us awareness of their culture and helping to dispel commonly existent prejudices regarding their beliefs.